2016
DOI: 10.1108/s2045-060520160000005009
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Sustainable Innovation in Agri-Food Supply Chains

Abstract: This chapter introduces the volume's theme by describing the challenges of sustainability in the agri-food industry and the critical role of agri-food supply chains. Following a description of traditional and sustainable supply chain management practices, we discuss the likely characteristics of sustainability oriented innovations and how organizations pursuing higher levels of economic, social, and environmental performance will need to adapt their capabilities. Design/Approach/Methodology: Drawing on the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The fourth hypothesis test research revealed that there is a positive and significant relationship between innovation and sustainable competitive advantage. The result was consistent with the study results of Cagliano et al (2016), Chong et al (2011), and Gualandri and Kalchschmidt (2014). Therefore, innovation capabilities help organizations create and develop internal activities, such as supply chain management, to achieve sustainable competitive advantage.…”
Section: Discussionsupporting
confidence: 93%
“…The fourth hypothesis test research revealed that there is a positive and significant relationship between innovation and sustainable competitive advantage. The result was consistent with the study results of Cagliano et al (2016), Chong et al (2011), and Gualandri and Kalchschmidt (2014). Therefore, innovation capabilities help organizations create and develop internal activities, such as supply chain management, to achieve sustainable competitive advantage.…”
Section: Discussionsupporting
confidence: 93%
“…Researchers suggested that pressures as well as incentives are needed from governmental as well as non-governmental agencies to motivate sustainable initiatives in the agri-food sector (Bloom, 2015). As such, the enablers in the cause group based on their impact can be given as the 'Understanding the sustainability initiative importance and benefits (E4)', with (R-C) score of 0.83, helps in developing research and development practices in sustainable agri-food value chains (Cagliano et al, 2016). Next, 'Management involvement, support and commitment (E5)' is very important to make efficient resource allocation and enable sharing of strategic information for eco-friendly practices among supply chain members (Yakovleva et al, 2012).…”
Section: Phase 3: Categorization Of the Identified Enablers Into Causmentioning
confidence: 99%
“…The protean nature of sustainability comes from the definition of each pillar. Furthermore, interactions between each pillar emphasize the need to understand the extent to which SFSCs are likely to promote the performance and subsistence of farms (Cagliano et al, 2016).…”
Section: General Frameworkmentioning
confidence: 99%